Relationship between Body Mass Index and Bone Mineral Density assessed by Dual-Energy X-ray Absorptiometry Scan: Single Institute based Experience (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Osteoporosis is a metabolic skeletal disease characterized by bone mineral density reduction, leading to increased susceptibility to fractures. Although several studies have investigated the association between body mass index (BMI) and bone mineral density (BMD), the results are inconsistent. The aim of this study was to further investigate the relation between BMI and BMD. Patients and Methods: The retrospective study included 113 patients without any apparent illness referred to have a dual-energy x-ray absorptiometry (DEXA) examination in INMAS, Suhrawardy, in the period from October 2023 to November 2024. The following anthropometric data were collected: body mass index, body weight, height, dual-energy x-ray absorptiometry T-score, and bone mineral density (BMD), as well as some other data. Results: The mean age was 56.17 years, the mean weight was 59.97 kg, and the mean height was 158.1 cm. There were 70 participants in the group of normal body mass index < 25.0 kg/m2, 34 participants were overweight (BMI 25.0-30.0 kg/m2), and 09 were obese (BMI > 30 kg/m2). In the obese group, 55.56% of participants had osteoporosis, 33.33% had osteopenia, and 11.11% had the normal T-score. In the overweight group, 14.71% of the participants had osteoporosis, 26.47% had osteopenia, and 58.82% had the normal T-score. In the normal body mass index group, 32.86% of the participants had osteoporosis, 34.29% had osteopenia, and 32.86% had the normal T-score. Conclusion: This study reveals that the prevalence of osteoporosis and osteopenia is higher in obese patients. It is obvious that there was a stronger correlation between body mass index and bone mineral density of the lumbar spine than between body mass index and bone mineral density of the total hip.Bangladesh J. Nuclear Med. 27(2): 253-259, 2024